2018
DOI: 10.15694/mep.2018.0000271.1
|View full text |Cite
|
Sign up to set email alerts
|

Selection and lottery in medical school admissions: who gains and who loses?

Abstract: Concerns related to fairness of medical school admissions through selection have led some scholars to consider selection as an expensive lottery and suggest that lottery may be fairer. This paper considers the issue of selection versus lottery from the perspectives of three groups of stakeholders: 1) applicants, 2) medical schools, and 3) society. This paper contributes to the discussion by addressing advantages and disadvantages of the use of selection and lottery for these stakeholder groups, grounded in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 60 publications
0
13
0
1
Order By: Relevance
“…Recent increases in medical school diversity can be attributed to changes in selection criteria, recruitment programs, and more equitable entry requirements 15 . Schools have experimented with selection criteria, such as blinding Medical College Admission Test (MCAT) scores, offering combined degrees that do not require the MCAT, and even using a lottery system in certain countries [16][17][18] . While the MCAT historically has been shown to have no cultural bias, some authors have alluded to the differences in average scores being a result of institutional racism 19,20 .…”
Section: Medical Schoolmentioning
confidence: 99%
“…Recent increases in medical school diversity can be attributed to changes in selection criteria, recruitment programs, and more equitable entry requirements 15 . Schools have experimented with selection criteria, such as blinding Medical College Admission Test (MCAT) scores, offering combined degrees that do not require the MCAT, and even using a lottery system in certain countries [16][17][18] . While the MCAT historically has been shown to have no cultural bias, some authors have alluded to the differences in average scores being a result of institutional racism 19,20 .…”
Section: Medical Schoolmentioning
confidence: 99%
“…8 There is sufficient reason to assume that underrepresentation of non-traditional students is a global phenomenon, as evidence suggests that opportunities to enrol in HPE programmes are not equally available to all eligible students 9 10 : those with non-traditional backgrounds face barriers in selection procedures, and there are indications that they tend to shy away from applying to HPE programmes. [11][12][13][14] The latter is called self-selection. Self-selection refers to students deciding to apply or not based on the information they have 15 and how they estimate their chance of success based on actual and perceived barriers and facilitators.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…These students can also become demotivated by the inequality they perceive. 14 However, the exact mechanisms behind how access to these social networks in healthcare can facilitate potential applicants are not clear. Other studies employing qualitative social network analyses in HPE have shown the importance of social networks of medical students in how they transition from preclinical to clinical training, and their networks’ role in accessing opportunities to learn 29 ; the influence of social networks on academic performance in medical school, 30 and how (not) having family members working in the medical field results in medical students being either ‘insiders’ versus ‘social newcomers’ to medicine.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of evidence of reliable selection methods that increase diversity, moving away from existing MSTS measures may leave URMs worse off [44], particularly if specialty programs revert to methods such as alumni networks, letters of recommendation, or other techniques that are biased towards those with greater resources. While acknowledging the trade-offs between the interests of patients, minorities, and society in general, some have argued that this lack of evidence justifies selection into medical training by a weighted lottery as the only existing method likely to be effective in achieving truly equitable levels of diversity in medical workforces [70].…”
Section: Lessons For Global Health Systemsmentioning
confidence: 99%